LiMn2O4 cathode materials with large porous structure and radial interior channels for lithium ion batteries. (10th September 2016) - Lu, Jia; Zhou, Cuifeng; Liu, Zongwen; Lee, Kim Seng; Lu, Li
Graphical abstract: Abstract: Macroporous spinel-structured LiMn2 O4 microparticles have been successfully prepared by a facile template-free synthesis process. Morphological characterization shows that the porous particles with size of about 4 μm are composed of small primary particles of about 200 nm with many tiny channels inside the microparticles. Electrochemical measurements reveal that the porous LiMn2 O4 cathode has a high specific capacity and superior high rate performance. It exhibits a reversible discharge capacity of about 132.9 mAh g −1 at a low charge/discharge rate of 0.1C. When tested at high rates of 20C and 50C, the discharge capacities still remain at 106 and 67 mAh g −1, respectively. Furthermore, the porous LiMn2 O4 possesses excellent cyclability. All the results suggest this porous LiMn2 O4 to be highly promising for wide application in high power lithium ion batteries.